1995
DOI: 10.1029/94je02801
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic obliquity and the nature of the Martian climate

Abstract: Recent calculations of the Martian obliquity suggest that it varies chaotically on timescales longer than about 107 years and varies between about 0 and 60°. We examine the seasonal water behavior at obliquities between 40 and 60°. Up to several tens of centimeters of water may sublime from the polar caps each year, and possibly move to the equator, where it is more stable. CO2 frost and CO2‐H2O clathrate hydrate are stable in the polar deposits below a few tens of meters depth, so that the polar cap could con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 34 publications
3
122
0
Order By: Relevance
“…According to Jakosky et al (1995), several of the various ternary salt waters had freezing points below 225 K and Martian brines may have existed in the past and even now. Therefore, if seepage groundwater is in pure H 2 O form, or contains only sulfate and chloride salts, the water would likely freeze while seeping to the surface of presentday Mars.…”
Section: Potential Antifreeze Compoundsmentioning
confidence: 99%
“…According to Jakosky et al (1995), several of the various ternary salt waters had freezing points below 225 K and Martian brines may have existed in the past and even now. Therefore, if seepage groundwater is in pure H 2 O form, or contains only sulfate and chloride salts, the water would likely freeze while seeping to the surface of presentday Mars.…”
Section: Potential Antifreeze Compoundsmentioning
confidence: 99%
“…[82] If the polar caps contain a significant amount of CO 2 clathrate admixed with water ice [Jakosky et al, 1995;Hoffman, 2000], then because CO 2 clathrate has a lower thermal conductivity and is stable under higher pressures than pure water ice, the cap would not melt as readily as it would if composed of pure water ice. Thus, obtaining an accurate estimate of the amount of CO 2 clathrate in the layered deposits would help constrain the conditions necessary for melting the deposits.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Several studies have suggested gas hydrate dissociation as a mechanism for forming surface erosional features [Hoffman, 2000;Max and Clifford, 2001], and as significant subsurface or polar reservoirs of ancient water, CO 2 , and CH 4 which may have contributed to a thicker greenhouse atmosphere early in Martian history [Jakosky et al, 1995;Miller and Smythe, 1970;Prieto-Ballesteros et al, 2006]. The likelihood of large-scale CH 4 or CO 2 hydrate deposits in the nearsubsurface, however, has been questioned based on thermal conductivity calculations [Mellon, 1996].…”
Section: Introductionmentioning
confidence: 99%